Lifestyle balance, restful and strenuous occupations, and physiological activation. Issue 4 (1st October 2020) - Hernandez, Raymond; Vidmar, Alaina; Pyatak, Elizabeth A.
ABSTRACT: A balance between stressful and restful occupations is an important component of lifestyle balance (LB). We argue that excessive physiological activation from the stress of everyday engagement in occupation, and/or inadequate engagement in restful occupations, can lead to negative health outcomes through accumulation of allostatic load (AL), or physiological wear and tear on the body. This physiological activation manifests as increased heart rate, blood pressure, and activation of the hypothalamic-pituitary-adrenal (HPA) axis, resulting in elevations in serum levels of hormones such as cortisol and catecholamines. "Stress, " as the term is used colloquially, is just one possible source of physiological activation. Other possible sources include cognitive challenges and high motivation tasks. The purpose of this paper is twofold: 1) to present an explanatory model for how the LB component of a "pattern of occupations with a balance between stressful and restful engagements" can affect health and 2) to discuss metrics to measure physiological activation from stress/rest and explore how these metrics relate to existing measures of lifestyle and occupational balance. We speculate that these metrics may relate to existing measures of lifestyle and occupational balance in ways that help explain the mechanisms underlying them, with the amount of physiological activation that individuals experience on a daily basis determining their long-term health outcomes. There remains a need to develop innovative lifestyle interventions that support management of stress related physiological activation to promote health and well-being.